The Judicial Use of International Human Rights Law in New Zealand - Butler, Petra; Butler, Andrew S (Victoria University of Wellington Law Review, 1999)
In this essay we briefly examine the judicial use of international human rights law in New Zealand. In particular, we identify the relevant sources of international human rights law for New Zealand and the possible methods of application of international human rights law in New Zealand’s domestic judicial system, we assess the actual significance accorded to international human rights law, and attempt to account for the marked increase in use of international human rights law by New Zealand judges.